The Influence of Digital Competency and Teacher Leadership on Innovative Behaviour and Teaching Performance in Jambi Province - Joni, Muhammad; Susanti, Nova; Hendra, Robi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to analyse the influence of digital competency and teacher leadership on innovative behaviour and teaching performance among teachers in Jambi Province, reflecting the growing demands of modern education that require teachers to adapt to technological advancements and demonstrate strong leadership within instructional settings. Using a quantitative approach, data were collected through a validated Likert-scale questionnaire distributed online to 218 teachers selected through quota sampling. The data were analysed using PLS-SEM to examine the strength and significance of the relationships among the variables. The results indicate that both digital competency and teacher leadership have a significant positive effect on innovative behaviour, suggesting that teachers who possess stronger digital skills and leadership abilities are more likely to initiate and adopt innovative practices in the classroom. However, the study also reveals that digital competency and innovative behaviour do not have a direct significant impact on teaching performance, implying that improvements in teaching performance may depend on other factors such as organizational support, school culture, workload, or policy frameworks that were not examined in this research. These findings highlight the importance of adopting a more comprehensive approach when seeking to enhance teaching performance, as digital proficiency and innovation alone may not be sufficient without supportive institutional conditions. The study contributes to the existing literature on digital competence, teacher leadership, and innovation in the Indonesian educational context and provides valuable insights for stakeholders in designing more effective professional development and instructional improvement programs.